Analisis Produktivitas Alat Angkut dan Muat Pada Pengupasan Overburden di PT. XYZ Desa Batuah, Kutai Kartanegara, Kalimantan Timur - Putri Indah Lestari; Ahsinlana Dzikrorrohman Farist (Program Studi Teknik Pertambangan Fakultas Teknik Universitas Jember, 2023)
PT. XYZ is a company engaged in coal mining contractors located in East Kalimantan. During mining activities, PT. XYZ uses an open-pit mining system. In February 2023 PT. XYZ had a production target overburden of 193,700 bcm, but in reality, the production target only reached 119,529 bcm.. The productivity of the conveyance and loading equipment is by field conditions to be compared with the company's production achievement targets. The research method used is a quantitative method where this research takes data directly and interviews in the field. The results of the calculation analysis, the production of means of conveyance dumptruckIVECO 350 reached 27.17 Bcm/hour, dump truck ISUZU GIGA FV285 reached 22.16 Bcm/hour, andarticulated dump truck VOLVO A40G achieved 54.57 Bcm/hr. Production of the Sanny SY330H excavator truck reached 178.63 Bcm/hour and the XCMG X370CA excavator reached 154.09 Bcm/hour. The amount of production of the actual means of conveyance that was achieved was 193,700 Bcm/hour. The parameters that affect the amount of production of a tool both hauling and loading, namely circulation time, tub or bucket capacity, amount of filling, fill factor, and material expansion factor. However, based on field observations by the author, there are several additional factors such as the type of weather factor and the condition of the mine road or ramp. In addition to the weather factor, road conditions that are far from the existing standard size will affect the amount of production of a tool. Keywords: coal, Overburden, Production, productivity